Gender Moderation on Students’ Adoption of WhatsApp for Learning-Support Communication in Sub-Saharan Africa - Yeboah, Douglas; Nyagorme, Paul; Bervell, Brandford; Koi-Akrofi, Godfred Yaw; Bempong, Awo Esaah (Journal of educational technology development and exchange, 2025)
Gender moderation in students’ adoption of WhatsApp for supporting distance learning has not been explored. This study applied the Unified Theory of Acceptance and Use of Technology model to analyze the moderation effects of gender on students’ adoption intentions of WhatsApp for learning. Multi-stage sampling techniques were used to obtain 273 participants. Data were collected using structured questionnaire and analyzed using partial least squares structural equation modeling. Results showed that gender significantly moderated the effects of(a) performance expectancy on behavioral intention such that the effect was stronger for males than females, and (b) social influence on behavioral intention such that the effect was stronger for females than males. Effects of effort expectancy, mobile self-efficacy, and facilitating conditions on behavioral intention were not moderated by gender. Implications of the findings for practice were discussed and recommendations were made for further research.